Oral bait handout as a method to access roaming dogs for rabies vaccination in Goa, India: A proof of principle study. (11th April 2019) - Gibson, A.D.; Yale, G.; Vos, A.; Corfmat, J.; Airikkala-Otter, I.; King, A.; Wallace, R.M.; Gamble, L.; Handel, I.G.; Mellanby, R.J.; Bronsvoort, B.M. de C.; Mazeri, S.
Abstract: Rabies has profound public health, social and economic impacts on developing countries, with an estimated 59, 000 annual human rabies deaths globally. Mass dog vaccination is effective at eliminating the disease but remains challenging to achieve in India due to the high proportion of roaming dogs that cannot be readily handled for parenteral vaccination. Two methods for the vaccination of dogs that could not be handled for injection were compared in Goa, India; the oral bait handout (OBH) method, where teams of two travelled by scooter offering dogs an empty oral bait construct, and the catch-vaccinate-release (CVR) method, where teams of seven travel by supply vehicle and use nets to catch dogs for parenteral vaccination. Both groups parenterally vaccinated any dogs that could be held for vaccination. The OBH method was more efficient on human resources, accessing 35 dogs per person per day, compared to 9 dogs per person per day through CVR. OBH accessed 80% of sighted dogs, compared to 63% by CVR teams, with OBH accessing a significantly higher proportion of inaccessible dogs in all land types. All staff reported that they believed OBH would be more successful in accessing dogs for vaccination. Fixed operational team cost of CVR was four times higher than OBH, at 127 USD per day, compared to 34 USD per day. Mean per dog vaccination cost of CVR was 2.53 USD, whilst OBH was 2.29 USD. Extrapolation to a two week India national campaign estimated that 1.1 million staff would be required using CVR, but 293, 000 staff would be needed for OBH. OBH was operationally feasible, economical and effective at accessing the free roaming dog population. This study provides evidence for the continued expansion of research into the use of OBH as a supplementary activity to parenteral mass dog vaccination activities in India.